Pengaruh Kompensasi, Lingkungan Kerja Fisik Dan Disiplin Kerja Terhadap Kinerja Karyawan - Pramana, A.A. Gede Kresnayana; Sudharma, I Nyoman (E-Jurnal Manajemen, 2013)
Performance is a very important thing for the institution. Employees who have a high performance must be able to work optimally so that the objectives of the institution itself will be easily achieved. For that institutions should consider the factors that may affect the performance of employees. In this research to determine the three variables that can affect the performance of the employee, the variable compensation, physical work environment, and work discipline. The variables studied to determine the effect of simultaneous or partially on the employee's performance on the LPD Jimbaran Village People with multiple linear regression analysis as an analytical technique. Besides the physical working environment variable is a variable that dominant influence on employee performance seen from the Standardized Beta Coefficients with the highest value.